Sport science relevance and application: Perceptions of UK coaches - Martindale, R.; Nash, C. (Journal of Sports Sciences, 2013)
While sport science can have significant and positive impact on coaches and athletes, there is still a general consensus that the transfer of sport science knowledge to coaching is poor. Given this apparent dilemma, this study investigated the perceptions of sport science from coaches across four different sports (football, rugby league, curling and judo) across three different levels (elite, developmental and novice). Specifically, 58 coaches (19 football; 21 rugby league; 9 curling; 9 judo) drawn evenly from novice, developmental and elite groups agreed to take part and were interviewed. Three key features emerged from the analysis 1) Practical application and relevance 2) Integration and access, 3) Language. In short, there was significant variability in the extent to which sport science was considered relevant and to whom, although interestingly this was not strongly related to coaching level. This inconsistency of understanding was a barrier to sport science engagement in some instances, as was the challenge of operationalising information for specific contexts. Furthermore, availability of opportunities and resources were often left to chance, while overuse of jargon and inability for research and practitioners to consider sport specific needs were also considered barriers to engagement. Implications for research and practice are discussed.